1950
DOI: 10.1103/physrev.79.490
|View full text |Cite
|
Sign up to set email alerts
|

Decay Constants ofK40

Abstract: gested several of the chemical separations. Thanks are also due Mr. Bernie Rossi and the 60-inch cyclotron crew for carrying out the bombardments. APPENDIX. CHEMICAL PROCEDURETo the solution of Mn in HC1 10 mg amounts of Co, Cu, Fe, Ni, Zn carriers were added. The IN solution was saturated with (NHJsSCN and shaken with a 50 percent mixture of diethyl ether and amyl alcohol. After several washings the alcohol-ether extract was found to be free of Mn. The remaining metals were removed I. INTRODUCTIONOOTASSIUM 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1950
1950
1961
1961

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Its use in this laboratory to coat VYNS source-mounting films with gold has already been described (15). Further it has already been used to mount radioactive materials both for beta-spectrometry (10,19) and in 4n-counters (6,21). However no regular use of it nor any attempt to employ it in the present way for selfabsorption studies has been reported.…”
Section: B Experimental Techniques and Resultsmentioning
confidence: 99%
“…Its use in this laboratory to coat VYNS source-mounting films with gold has already been described (15). Further it has already been used to mount radioactive materials both for beta-spectrometry (10,19) and in 4n-counters (6,21). However no regular use of it nor any attempt to employ it in the present way for selfabsorption studies has been reported.…”
Section: B Experimental Techniques and Resultsmentioning
confidence: 99%
“…The results indicate a half-life of 65=fc3 days, in good agreement with the value reported by DuBridge and Marshall. 1 The secondary electrons ejected from a 50-mg/cm 2 uranium radiator shows K and L shell photo-electron peaks for the 65-day activity, corresponding to a gamma-ray of energy 513=1=3 kev. This was at first thought to be annihilation radiation.…”
Section: Nobel Institute Of Physics Stockholm Swedenmentioning
confidence: 99%
“…1 Pm 149 further decays with a half-life of about 2 days. 1 "Specpure" Nd 2 0 3 was irradiated by slow neutrons in the Harwell pile for 4 weeks, and the resulting activities were studied at this Institute using a 0-ray spectrometer. 2 Finely powdered Nd2C>3 was spread with an average thickness of about 2 mg/cm 2 over an aluminum backing of 2 mg/cm 2 .…”
Section: Nobel Institute Of Physics Stockholm Swedenmentioning
confidence: 99%
“…Swiss Federal Institute of Technology, Zurich, Switzerland (Received July 9,1951) A N electron bound to an impurity is usually treated like a hydrogen atom in which the electrostatic force is reduced by the dielectric constant c of the crystal. 1 We shall use a more detailed treatment for a phosphorus impurity in silicon.…”
Section: Walter Baltenspergermentioning
confidence: 99%